The Effect of the Use of Visual-Based Learning Media in Improving Chemistry English Vocabulary Mastery in Chemistry Education Students - Burhan, Kristian; Yuhelman, Nofri (The Future of Education Journal, 2025)
The purpose of this study is to empirically examine how using visual-based learning materials can help students in chemistry education programs become more proficient in English vocabulary. This quasi-experimental study involved 60 Universitas Negeri Padang second semester chemistry education students. The experimental group (n=30) received chemical English vocabulary instruction using visual-based learning materials, while the control group (n=30) received instruction using traditional text-based techniques. Participants were randomly assigned to one of two unequal groups. Valid and trustworthy pre-test and post-test tools were used to gather data on vocabulary mastery. The experimental group demonstrated a significantly greater increase (p < 0.05) in vocabulary mastery scores than the other group, according to data analysis using the independent samples t-test. According to the study's findings, using visual-based learning resources can help students comprehend, remember, and become proficient in important chemical English vocabulary. This can help them better comprehend English chemistry literature and get ready for chemistry-related problems around the world.